Granulated powder for MnZn ferrite and method for producing the same, and MnZn ferrite and method for producing the same
By optimizing the composition and process of MnZn-based ferrite, the problem of low break load during car loading is solved, high break load and good magnetic characteristics are achieved, and the stability and performance of the magnetic core of the automotive electronic components is ensured.
Patent Information
- Application Number
- CN202380013893.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-17
- Filing Date
- 2023-10-12
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-10-12
AI Technical Summary
The existing MnZn-type ferrite has low breakage load during automobile installation, easy to breakage, and it is difficult to take into account high breakage load and good magnetic characteristics.
By optimizing the composition of MnZn system ferrite, the optimal composition ratio of Fe2O3 and ZnO is increased, and non-magnetic components such as SiO2, CaO and Nb2O5 are added to generate uniform grain boundaries, increase resistivity, and reduce loss value. At the same time, through improvement The molding process of granulation powder reduces friction and suppresses the occurrence of cracks.
The high fracture load and good magnetic characteristics of the MnZn-based ferrite are achieved, ensuring the stability and performance of the magnetic core of the automotive electronic components, and avoiding electronic component failures caused by ferrite damage.
Smart Images

Figure CN118830036B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a MnZn-based ferrite particularly suitable for use in a magnetic core of an automobile-mounted component, a granulated powder for the MnZn-based ferrite, and a method for producing the same. Background Art
[0002] MnZn ferrite is a material widely used as a core for noise filters, transformers, and antennas in switching power supplies, etc. The advantages of MnZn ferrite include high magnetic permeability and low loss in the kHz region among soft magnetic materials, and low price compared to amorphous metals, etc.
[0003] With the recent development of hybrid and electrified automobiles, the demand for MnZn ferrites used in the magnetic cores of electronic components for automobiles has increased, and high breaking loads are required. This is because MnZn ferrites are ceramics and brittle materials, so they are easily damaged. In addition, compared with existing home appliance applications, they are constantly subjected to vibrations and are continuously used in an environment that is prone to damage.
[0004] If ferrite with a low breaking load is mixed into a product, the ferrite may be damaged and the car itself may become inoperable, so preventing the mixing (appearance) of defective products with a low breaking load is an important issue.
[0005] On the other hand, in automobile applications, weight reduction and space saving are also required, and therefore, in addition to having a high breaking load, it is important to have good magnetic properties as in conventional applications.
[0006] Various MnZn-based ferrites for automobile applications have been developed in the past in response to the above-mentioned needs. Among ferrites having excellent magnetic properties, the inventions described in Patent Documents 1 and 2 are exemplified.
[0007] Furthermore, as a MnZn-based ferrite having improved mechanical properties in addition to magnetic properties, the invention described in Patent Document 3, for example, has been reported.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2007-51052;
[0011] Patent Document 2: Japanese Patent Application Publication No. 2012-76983;
[0012] Patent document 3: Japanese Patent No. 6730545. Summary of the invention
[0013] Problem that the invention aims to solve
[0014] However, for example, in the technologies described in Patent Documents 1 and 2, although compositions for achieving desired magnetic properties are mentioned, the fracture toughness value is not described at all, and problems still exist as magnetic cores for automotive electronic components.
[0015] On the other hand, Patent Document 3 mentions the improvement of mechanical properties in addition to magnetic properties, but only describes the fracture toughness value as a material property. Here, the fracture load of the ferrite core is affected not only by the material properties but also by the properties of the starting point of the breakage, and is therefore affected by the stability of the manufacturing process and product defects. That is, from the perspective of preventing defective products with low fracture load and manufacturing products with stable quality, it is not sufficient to control the fracture toughness value alone.
[0016] The present invention has been made in view of the above circumstances, and its object is to provide a MnZn ferrite and a granulated powder for the MnZn ferrite, and a method for producing the same, wherein the MnZn ferrite has: an M strength of a sintered body E42 / 15 of JIS C2560 with a long side of 42 mm, a short side of 21 mm, and a thickness of 15 mm, with an average value of high and excellent mechanical properties in which no sample with significantly low strength occurs; and a loss value of 380 kW / m at 100°C, 100 kHz, and 200 mT for a ring-shaped core produced under the same conditions. 3 The following good magnetic properties.
[0017] Solutions for solving problems
[0018] The inventors have conducted intensive studies to achieve the above-mentioned objects and have obtained the following findings.
[0019] That is, the inventors first discovered the optimal composition of Fe2O3 and ZnO in MnZn ferrite that can reduce the loss value at 100°C, 100kHz and 200mT. Within this composition range, the magnetic anisotropy and magnetostriction are small, the resistivity is maintained, and the secondary peak that makes the temperature characteristic of the loss show a minimum value can also appear near 100°C, so low loss at 100°C, 100kHz and 200mT can be achieved.
[0020] In addition, it was found that by adding appropriate amounts of SiO2, CaO and Nb2O5, which are non-magnetic components that segregate at grain boundaries, uniform grain boundaries can be generated, the resistivity can be increased, and the loss value can be further reduced.
[0021] In addition, regarding the mechanical properties of MnZn-based ferrites, effective factors for increasing the average value of M strength and preventing samples with significantly low strength from occurring were investigated, and the following findings were obtained.
[0022] That is, the inventors investigated the cause of the reduction in M strength and focused on the fact that there was a pre-existing crack at the root of the center column of the core body, which was the starting point of damage. As the length of the crack increased, the M strength showed a tendency to decrease. Next, the manufacturing process that caused the pre-existing crack was investigated, and it was found that the pre-existing crack already existed when the granulated powder was pressed into powder to produce a molded body.
[0023] Therefore, focusing on the powder pressing molding process, the results show that: the friction force generated between the granulated powders during molding varies depending on the shape and surface properties of the granulated powders being molded, and therefore the propagation behavior of the molding pressure is different; in addition, the greater the friction force, the greater the deviation in the local molding density inside the molded body, so there is a difference in the expansion rate during demolding, and cracks are more likely to occur at the root of the center column of the magnetic core.
[0024] Next, a method for quantifying the magnitude of friction between granulated powders was investigated. The results showed that when the fluidity of powders was numerically converted into torque using a powder rheometer capable of measuring the fluidity of powders between the uncompacted smooth filling state and the state after 20 vibrations, which is the state for measuring the loose bulk density of powders, if the ratio obtained by dividing the torque value after 20 vibrations by the torque value in the uncompacted smooth filling state (hereinafter also referred to as "torque ratio") is above a certain value, the friction of the granulated powder is small and the moldability is excellent, the local distribution of the molding density can be suppressed, and the occurrence of cracks can be suppressed.
[0025] The mechanism can be inferred as follows.
[0026] Figure 1 (a) shows a microscopic observation image of a granulated powder having a large friction force and having a large number of small cotton-like objects attached to the surface of the granulated powder (Comparative Example 3-1 described later). Figure 1 (b) shows a microscopic observation image of a granulated powder (Inventive Example 1-2 described later) having a smooth surface without any cotton-like substance attached thereto and having a low friction force. Figure 1 In the state shown in (a), since the friction between the granulated powders is large, the resistance to the rotational force of the blade of the powder rheometer becomes small after 20 times of compaction, and the torque value of the blade of the powder rheometer is detected to be low. Figure 1 As shown in (b), when the surface of the granulated powder is smooth and the friction between the granulated powders is small, the torque value of the blade of the powder rheometer detected after 20 tappings is high.
[0027] Therefore, the friction force on the surface of the granulated powder can be quantified in the form of the ratio of the torque values of the powder viscosity before and after the compaction operation. By setting regulations for this numerical value, the occurrence of cracks in the molding process can be suppressed, and the average value of the M strength of the sintered core obtained is high, and the occurrence of a core with significantly low M strength can also be suppressed.
[0028] The present invention has been accomplished based on the above findings. That is, the main configuration of the present invention is as follows.
[0029] [1] A granulated powder for MnZn-based ferrite, comprising an iron compound, a zinc compound, a manganese compound, a silicon compound, a calcium compound, a niobium compound and inevitable impurities, wherein when the total amount of the iron compound, the zinc compound and the manganese compound is 100 mol % in terms of Fe2O3, ZnO and MnO, the iron compound is 51.5 to 56.8 mol % in terms of Fe2O3 and the zinc compound is 5.0 to 15. 5mol%, and the above-mentioned manganese compound is calculated as MnO as the balance, relative to the total amount of the above-mentioned iron compound, the above-mentioned zinc compound, and the above-mentioned manganese compound, the above-mentioned silicon compound is calculated as SiO2 conversion amount of 50 to 300 mass ppm, the above-mentioned calcium compound is calculated as CaO conversion amount of 100 to 1300 mass ppm, and the above-mentioned niobium compound is calculated as Nb2O5 conversion amount of 100 to 400 mass ppm, and the torque ratio of the above-mentioned MnZn-based ferrite granulated powder is 1.7 or more.
[0030] [2] The granulated powder for MnZn-based ferrite according to [1] above, wherein the granulated powder for MnZn-based ferrite further contains at least one of a cobalt compound and a nickel compound, and the amount of the cobalt compound is 3500 mass ppm or less in terms of CoO conversion, and the amount of the nickel compound is 15000 mass ppm or less in terms of NiO conversion, relative to the total amount of the iron compound, the zinc compound and the manganese compound.
[0031] [3] A method for producing granulated powder for MnZn-based ferrite, which is a method for producing the granulated powder for MnZn-based ferrite described in [1] above, the method comprising the following steps: a pre-calcining step, in which a mixture of an iron compound, a zinc compound and a manganese compound is pre-calcined to obtain a pre-calcined powder; a mixing-crushing step, in which a silicon compound, a calcium compound and a niobium compound are added to the pre-calcined powder, the mixture is mixed, and the mixture is crushed to obtain a crushed powder; an impregnation step, in which the crushed powder is impregnated in an alkaline aqueous solution; and a granulation step, in which a binder is added to the crushed powder after the impregnation step, the mixture is mixed, and the mixture is granulated to obtain a granulated powder.
[0032] [4] A method for producing granulated powder for MnZn-based ferrite, which is a method for producing the granulated powder for MnZn-based ferrite described in [2] above, the method comprising the following steps: a pre-calcining step, in which a mixture of an iron compound, a zinc compound and a manganese compound is pre-calcined to obtain a pre-calcined powder; a mixing-crushing step, in which a silicon compound, a calcium compound and a niobium compound are added to the pre-calcined powder, and at least one of a cobalt compound and a nickel compound is further added, mixed, and crushed to obtain a crushed powder; an impregnation step, in which the crushed powder is impregnated in an alkaline aqueous solution; and a granulation step, in which a binder is added to the crushed powder after the impregnation step, the mixture is mixed, and then granulated to obtain a granulated powder.
[0033] [5] A MnZn ferrite comprising a basic component, an auxiliary component and inevitable impurities, wherein, when the total amount of iron, zinc and manganese calculated as Fe2O3, ZnO and MnO is 100 mol%, iron calculated as Fe2O3 accounts for 51.5 to 56.8 mol%, zinc calculated as ZnO accounts for 5.0 to 15.5 mol%, and manganese accounts for the remainder as MnO, and among the auxiliary components, SiO2 accounts for 50 to 300 mass ppm, CaO accounts for 100 to 1300 mass ppm, and Nb2O5 accounts for 100 to 400 mass ppm relative to the basic component, and the minimum value of M strength measured for 100 samples of sintered bodies of type E42 / 15 conforming to JIS C2560-3-1:2006 exceeds 300 N, and the average value is 600 N or more.
[0034] [6] The MnZn-based ferrite according to [5] above, wherein the auxiliary component further contains at least one of 3500 mass ppm or less of CoO relative to the basic component and 15000 mass ppm or less of NiO relative to the basic component.
[0035] [7] The MnZn ferrite according to [5] or [6], wherein the loss value of the MnZn ferrite at 100°C, 100kHz and 200mT is 380kW / m 3 the following.
[0036] [8] A method for producing MnZn ferrite, which is a method for producing the MnZn ferrite described in [5] above, the method comprising the following steps: a pre-calcination step, in which a mixture of an iron compound, a zinc compound and a manganese compound is pre-calcined to obtain a pre-calcined powder; a mixing-crushing step, in which a silicon compound, a calcium compound and a niobium compound are added to the pre-calcined powder, the mixture is mixed and then crushed to obtain a crushed powder; an impregnation step, in which the crushed powder is impregnated in an alkaline aqueous solution; a granulation step, in which a binder is added to the crushed powder after the impregnation step, the mixture is mixed and then granulated to obtain a granulated powder; and a sintering step, in which the granulated powder is molded to obtain a molded body, and the molded body is sintered to obtain MnZn ferrite.
[0037] [9] A method for producing MnZn ferrite, which is a method for producing the MnZn ferrite described in [6] above, the method comprising the following steps: a pre-calcining step, pre-calcining a mixture of an iron compound, a zinc compound and a manganese compound to obtain a pre-calcined powder; a mixing-crushing step, adding a silicon compound, a calcium compound and a niobium compound to the pre-calcined powder, and further adding at least one of a cobalt compound and a nickel compound, mixing, and crushing to obtain a crushed powder; an impregnation step, impregnating the crushed powder in an alkaline aqueous solution; a granulation step, adding a binder to the crushed powder after the impregnation step, mixing, and granulating to obtain a granulated powder; and a sintering step, molding the granulated powder to obtain a molded body, and then sintering the molded body to obtain MnZn ferrite.
[0038] Effects of the Invention
[0039] According to the present invention, it is possible to provide a MnZn ferrite having: an M strength of a sintered body E42 / 15 of an E-type core having a long side of 42 mm, a short side of 21 mm, and a thickness of 15 mm according to JIS C2560, in which the average value is high and there is no sample with significantly low strength; and a loss value of 380 kW / m at 100°C, 100 kHz, and 200 mT for a ring-shaped core produced under the same conditions. 3 The following good magnetic properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 (a) is a microscope observation image of a granulated powder having a large friction force and many small cotton-like objects attached to the surface of the granulated powder (Comparative Example 3-1). Figure 1 (b) is a microscopic observation image of a granulated powder (Inventive Example 1-2) having a smooth surface without any cotton-like substance attached thereto and having a low friction force. DETAILED DESCRIPTION
[0041] Generally, in order to reduce the loss value of MnZn ferrite, it is effective to reduce magnetic anisotropy and magnetostriction. Moreover, in order to achieve this, it is necessary to select the blending amount of Fe2O3, ZnO and MnO, which are the main components of MnZn ferrite, from an appropriate range. In addition, by applying sufficient heat in the sintering process of the MnZn ferrite, the grains in the ferrite are appropriately grown, so that the movement of the magnetic domain wall in the grains in the magnetization process can be facilitated. Furthermore, in the present invention, by adding a component that segregates at the grain boundary, a grain boundary of moderate and uniform thickness is generated, thereby maintaining the resistivity and reducing the eddy current loss, thereby achieving low loss in the 100-500kHz region.
[0042] In addition to the above-mentioned magnetic properties, the magnetic core of the electronic components used in automobiles is also required to have a stable and high breaking load so that it will not break even in an environment that is constantly subjected to vibration. This is because: if the MnZn-based ferrite used as the magnetic core is damaged, the inductance will be greatly reduced, and the electronic component will not be able to play the expected role. Therefore, the entire car may not be able to operate.
[0043] Therefore, MnZn ferrites used in automotive electronic components are required to have both low-loss magnetic properties and a high and stable breaking load value. According to the present invention, MnZn ferrites having both good magnetic properties and breaking load values can be provided.
[0044] The following further describes the embodiments of the present invention. In addition, the present invention is not limited to the following embodiments. In addition, in this specification, the numerical range represented by "to" includes the numerical values recorded before and after "to" as the lower limit and upper limit, respectively.
[0045] In the present invention, the composition of MnZn ferrite is limited. First, the reason why the composition of MnZn ferrite (hereinafter, also referred to as ferrite) is limited to the following range in the present invention is explained. In addition, iron, zinc, and manganese contained in the present invention as basic components are expressed in values converted to Fe2O3, ZnO, and MnO, respectively. In addition, the content of these Fe2O3, ZnO, and MnO is expressed in mol% when the total amount of iron, zinc, and manganese converted to Fe2O3, ZnO, and MnO is 100mol%. Furthermore, the content of auxiliary components and unavoidable impurities is expressed in mass ppm relative to the above-mentioned basic components.
[0046] The basic components are described below.
[0047] Fe2O3: 51.5~56.8mol%
[0048] In the basic components, whether Fe2O3 is less than or more than the appropriate amount, the magnetic anisotropy becomes larger and the magnetostriction also becomes larger, which leads to increased loss. Therefore, the content of Fe2O3 is 51.5 mol% or more and 56.8 mol% or less. The content of Fe2O3 is preferably 56.7 mol% or less.
[0049] ZnO: 5.0~15.5mol%
[0050] When the amount of ZnO is less than the appropriate range, the Curie temperature becomes too high, so the loss value at 100°C increases. Therefore, the minimum amount of ZnO is 5.0 mol%. The content of ZnO is preferably 5.5 mol% or more. On the other hand, when the content of ZnO is more than the appropriate range, the loss value at 100°C increases because the secondary peak temperature at which the loss value shows a minimum value decreases. Therefore, the upper limit of the ZnO content is 15.5 mol%. The content of ZnO is preferably 15.0 mol% or less.
[0051] MnO: Balance
[0052] In the present invention, the balance of the basic component of the MnZn ferrite is MnO. This is because if the balance is not MnO, the loss value under the excitation conditions of 100°C, 100kHz, and 200mT will not be 380kW / m 3 In addition, the content of MnO is preferably 30.0 mol% or more, and more preferably 30.5 mol% or more. In addition, the content of MnO is preferably 43.0 mol% or less, and more preferably 42.0 mol% or less.
[0053] The basic components have been described above, and the auxiliary components are as follows.
[0054] SiO2: 50-300 ppm by mass
[0055] It is known that SiO2 contributes to the homogenization of the crystal structure of ferrite. By adding SiO2 in an appropriate amount, abnormal grain growth can be suppressed and resistivity can be improved. In addition, with the appropriate addition of SiO2, the loss value under the excitation conditions of 100°C, 100kHz, and 200mT can be reduced. Therefore, a minimum of 50 mass ppm of SiO2 is contained. On the other hand, when the content of SiO2 is too much, abnormal grains will appear, causing the loss value to deteriorate significantly. Therefore, the content of SiO2 is set to 300 mass ppm or less. The content of SiO2 is preferably 55 mass ppm or more, and more preferably 60 mass ppm or more. In addition, the content of SiO2 is preferably 275 mass ppm or less, and more preferably 250 mass ppm or less.
[0056] CaO: 100-1300 mass ppm
[0057] Cao has the effect of segregating at the grain boundaries of MnZn ferrites and inhibiting grain growth. By adding an appropriate amount of Cao, the resistivity can be increased and the loss value under the excitation conditions of 100°C, 100kHz, and 200mT can be suppressed. Therefore, a minimum of 100 mass ppm of CaO is contained. On the other hand, when the CaO content is too much, abnormal grains will appear, which will deteriorate the loss value. Therefore, the CaO content is set to 1300 mass ppm or less. The CaO content is preferably 120 mass ppm or more, more preferably 150 mass ppm or more, and further preferably 200 mass ppm or more. In addition, the CaO content is preferably 1200 mass ppm or less, and more preferably 1100 mass ppm or less.
[0058] Nb2O5: 100~400 mass ppm
[0059] It is known that Nb2O5 has the effect of segregating at the grain boundaries of MnZn ferrites, slowly suppressing grain growth, and relieving the stress between grain boundaries caused by grain growth. Therefore, by adding Nb2O5 in an appropriate amount, the loss value can be reduced, so a minimum of 100 mass ppm of Nb2O5 is contained. On the other hand, when the content of Nb2O5 is too much, abnormal grains will appear, causing the loss value to deteriorate significantly, so the content of Nb2O5 is made to be less than 400 mass ppm. The content of Nb2O5 is preferably more than 120 mass ppm, more preferably more than 130 mass ppm. In addition, the content of Nb2O5 is preferably less than 380 mass ppm, more preferably less than 375 mass ppm, and further preferably less than 350 mass ppm.
[0060] The MnZn-based ferrite of the present invention may further contain the following additives as auxiliary components.
[0061] CoO: 3500 mass ppm or less
[0062] CoO contains Co with positive magnetic anisotropy. 2+ The CoO content is preferably 3500 ppm by mass or less, and the negative magnetic anisotropy of other components can be offset, and the initial magnetic permeability can be prevented from decreasing. The CoO content is more preferably 2500 ppm by mass or less.
[0063] NiO: 15000 mass ppm or less
[0064] NiO selectively enters the B position of the spinel lattice, increases the Curie temperature of the material, increases the saturation magnetic flux density, and as a result has the effect of reducing the loss value. The lower limit of the NiO content is not particularly limited, and can be 0 mass ppm, but in order to obtain this effect, it is preferably added to more than 1200 mass ppm, and more preferably to add more than 1500 mass ppm. More preferably, it is more than 2000 mass ppm. On the other hand, by making the NiO content less than 15000 mass ppm, the increase of magnetostriction can be further prevented, and the reduction of the loss value can be further prevented. Therefore, when adding NiO, it is preferred that the NiO content is less than 15000 mass ppm. More preferably, it is less than 12000 mass ppm.
[0065] Unavoidable impurities
[0066] The MnZn-based ferrite of the present invention contains inevitable impurities such as phosphorus, boron, and chlorine, but the content of these impurities is preferably suppressed to several hundred mass ppm or less.
[0067] The granulated powder for ferrite of the present invention contains an iron compound, a zinc compound, a manganese compound, a silicon compound, a calcium compound, a niobium compound, and inevitable impurities, and can contain at least one of a nickel compound and a cobalt compound as required.
[0068] When the total amount of the above-mentioned iron compound, the above-mentioned zinc compound and the above-mentioned manganese compound is 100 mol% in terms of Fe2O3, ZnO and MnO, the above-mentioned iron compound is 51.5-56.8 mol% in terms of Fe2O3, the above-mentioned zinc compound is 5.0-15.5 mol% in terms of ZnO, and the above-mentioned manganese compound is the remainder in terms of MnO.
[0069] The silicon compound is 50 to 300 mass ppm in terms of SiO2, the calcium compound is 100 to 1300 mass ppm in terms of CaO, and the niobium compound is 100 to 400 mass ppm in terms of Nb2O5, relative to the total amount of the iron compound, the zinc compound, and the manganese compound. Furthermore, the cobalt compound is 3500 mass ppm or less in terms of CoO, and the nickel compound is 15000 mass ppm or less in terms of NiO.
[0070] The reasons for limiting the content of each component are the same as those described in the description of each component of the ferrite.
[0071] In addition, in the present invention, for the granulated powder obtained in the manufacturing process described later, the ratio (torque ratio) of the dynamic fluidity (torque value) after 20 times of vibration measured by a powder rheometer to the dynamic fluidity (torque value) during loose bulk density filling without vibration needs to be 1.7 or more. As described above, when the torque ratio is 1.7 or more, the friction of the granulated powder is small and the moldability is excellent, the local distribution of the molding density can be suppressed, and the occurrence of cracks can be suppressed. In addition, the upper limit of the torque ratio is not particularly limited. In the granulated powder of the present invention, the torque ratio is approximately 2.50 or less.
[0072] The mechanism of the torque ratio and the reduction in core strength is considered to be as follows. That is, in the manufacturing process of MnZn-based ferrite, a powder pressing process is performed after the granulated powder is produced. However, if the friction between the powders is large at this time, the pressure from the mold pressurization is attenuated due to the friction between the granulated powders. In addition, it is not easy for the granulated powder to move to the gaps between the granulated powders in order to release the pressure. The behavior of rearrangement. As a result, the obtained molded body has a deviation in local density distribution, and the expansion rate of the molded body during demolding also has a deviation. In particular, when the deviation in the expansion rate is too large, the molded body cannot maintain the desired shape and cracks are generated. Since the cracks still remain after the molded body is sintered, they will induce a reduction in the strength of the ferrite core obtained by the sintering.
[0073] In contrast, in the present invention, it is important to perform an immersion treatment of immersing the pulverized powder in an alkaline aqueous solution. The immersion treatment is a treatment for imparting hydroxyl groups to the surface of the pulverized powder, which can increase the adhesion between the organic binder added to the granulated powder and the pulverized powder constituting the granulated powder, and the shape retention of the binder becomes stronger. Therefore, the amount of pulverized powder as primary particles that separates from the granulated powder is reduced, and a granulated powder with a smooth surface is finally obtained (refer to Figure 1 (b)).
[0074] The alkaline aqueous solution can be selected from ammonia water, ammonium carbonate aqueous solution, ammonium bicarbonate aqueous solution, etc. In addition, the alkaline aqueous solution preferably has a solute concentration of 0.01 mol / L or more, and more preferably has a solute concentration of 0.1 mol / L or more. The upper limit of the solute concentration of the alkaline aqueous solution is not particularly limited, and the solute concentration can be 5.0 mol / L or less. The weight of the alkaline aqueous solution is preferably a value of 0.20 or more when the weight of the alkaline aqueous solution is divided by the mass of the crushed powder, and more preferably 0.50 or more. The upper limit of this value is not particularly limited, and this value can be 1.50 or less. The time of the immersion treatment is not particularly limited, and is preferably 5 minutes or more, and can be 120 minutes or less.
[0075] If only the smoothness of the granulated powder surface is considered, the effectiveness of the alkaline aqueous solution is no different even if the components include metal and phosphoric acid components. However, the metal component does not decompose, scatter and remain in the subsequent sintering process like the non-metallic component. The residual metal component reacts with the components constituting the MnZn-based ferrite, affects the grain growth, and therefore hinders the realization of the desired magnetic properties. In addition, the same is true for the phosphoric acid component, and particularly the phosphorus component induces abnormal grain growth, so not only the desired magnetic properties cannot be obtained after the sintering process, but also the strength of the core is significantly impaired. Therefore, the components of the alkaline aqueous solution preferably include non-metallic components and do not include metal components and phosphoric acid components.
[0076] After the immersion treatment in the alkaline aqueous solution, the crushed powder is separated from the alkaline aqueous solution by filtering and other processes and recovered. The recovered crushed powder can be directly sent to the next process, or it can be dried and sent to the next process. The obtained immersion-treated crushed powder is slurried by adding water and a known organic binder such as polyvinyl alcohol, and is made into granulated powder by spray drying or the like.
[0077] In addition, as a secondary effect of reducing the friction of the granulated powder, the weight of the filling into the mold during molding can be stabilized. In particular, when the filling speed into the mold is increased, the weight of the granulated powder into the mold tends to become unstable, and the weight of the obtained product core tends to vary with each sample. By reducing the friction between the granulated powders, the weight variation of each sample can be suppressed.
[0078] In addition, various properties of MnZn ferrite are greatly affected by various parameters, not only the composition. Among them, the MnZn ferrite of the present invention has the following provisions in order to obtain magnetic properties and mechanical properties.
[0079] That is, in the MnZn ferrite of the present invention, the minimum value of the M strength measured for 100 samples of sintered bodies of model E42 / 15 conforming to JIS C2560-3-1:2006 (sintered bodies with long side: 42 mm, short side: 21 mm, thickness: 15 mm) exceeded 300 N, and the average value was 600 N or more. MnZn ferrite as a ceramic is a brittle material, and JIS C2560 stipulates not only magnetic properties but also strength. In particular, in automotive applications, since it is often used in an environment with vibration, a high-strength manufacturing method that does not break even when impacted and does not produce low-strength products is required. In the present invention, by satisfying the above-mentioned composition and various conditions of the granulated powder, the manufactured core body can effectively suppress cracks that become the starting point of breakage, and the average strength when measuring the M strength of 100 samples is above 600N, and the minimum value of the M strength exceeds 300N, that is, there is no low-strength core body with the M strength below 300N, and a core body with stable strength characteristics can be obtained.
[0080] Next, the method for producing the MnZn ferrite of the present invention is described. The method for producing the MnZn ferrite of the present invention includes the following steps: a pre-calcination step, in which the mixture of the above basic components is pre-calcined and cooled to obtain a pre-calcined powder; a mixing-crushing step, in which the above auxiliary components are added to the above pre-calcined powder and mixed, and then crushed to obtain a crushed powder; an impregnation step, in which the above crushed powder is impregnated in an alkaline aqueous solution; a granulation step, in which a binder is added to the crushed powder after being impregnated in the above alkaline aqueous solution and mixed, and then granulated to obtain a granulated powder; a molding step, in which the above granulated powder is molded to obtain a molded body; and a sintering step, in which the above molded body is sintered to obtain the MnZn ferrite.
[0081] In the manufacture of MnZn-based ferrite, first, the basic components of Fe2O3, ZnO and MnO powders are weighed separately in the above-mentioned ratio, and after they are fully mixed to form a mixture, the mixture is pre-calcined and cooled to form a pre-calcined powder (pre-calcination step).
[0082] The auxiliary components specified in the present invention are added to the pre-calcined powder obtained in this way according to a specified ratio, mixed, and pulverized (mixing-pulverization step). In this step, the powder is fully homogenized so that the concentration of the added components is uniform, and the pre-calcined powder is pulverized to a target average particle size (1.0 to 1.5 μm) to prepare a pulverized powder.
[0083] Next, the obtained pulverized powder is immersed in an alkaline aqueous solution, thereby implementing surface modification (immersion process). It is believed that this process plays a role in imparting hydroxyl groups to the surface of the pulverized powder. The imparted hydroxyl groups have the effect of improving the adhesion with the binder added during granulation as the next process. Therefore, the surface of the granulated powder obtained in this way is smooth and the friction between the granulated powders is small. During molding, the filling property is good and the rearrangement of the granulated powder during pressurization is easily promoted. It is not easy to have a difference in density distribution at various positions in the mold. Therefore, it is particularly possible to suppress the cracks of the molded body generated during demoulding. Therefore, the effect of suppressing the poor strength of the core product finally obtained can be obtained.
[0084] After the pulverized powder after the impregnation treatment is filtered to remove the alkaline aqueous solution, a known organic binder such as polyvinyl alcohol is added, and granulation is performed using a spray drying method to prepare a granulated powder (granulation step). At this time, regarding the dynamic fluidity when filled to the loose bulk density and after 20 taps, the obtained granulated powder satisfies the conditions within the above-mentioned numerical range.
[0085] Afterwards, the granulated powder is subjected to a sieving process for adjusting the particle size as required, and is molded by applying pressure in a molding machine to form a molded body (molding process). Next, the molded body is sintered under known sintering conditions to obtain the MnZn ferrite of the present invention (sintering process).
[0086] The above-mentioned MnZn-based ferrite can be subjected to processing such as surface polishing as appropriate.
[0087] The MnZn ferrite thus obtained has excellent mechanical properties that are not possible with conventional MnZn ferrites, namely, the M strength of the sintered body E42 / 15 with a long side of 42 mm, a short side of 21 mm, and a thickness of 15 mm measured in accordance with JIS C2560 for an E-type magnetic core is as high as an average value of more than 600 N, and there are no samples with significantly low strength of less than 300 N. In addition, the loss value of the ring-shaped core produced under the same conditions at 100°C, 100 kHz, and 200 mT is 380 kW / m 3 The following are good magnetic properties.
[0088] The loss value of the toroidal core was measured at 100°C, 100kHz, and 200mT using a core loss measuring instrument (SY-8232 manufactured by Iwatsu Instruments) after winding 5 turns of wire on the primary side and 5 turns of wire on the secondary side on the magnetic core.
[0089] In addition, regarding the strength of the sintered core, the M strength of the sintered body E42 / 15 with a long side of 42 mm, a short side of 21 mm, and a thickness of 15 mm was measured according to JIS C2560-3-1 (2006). 100 samples were measured for each standard, and the average value of the obtained values and the number of samples below 300 N were calculated.
[0090] In addition, the method for producing the sintered body (MnZn-based ferrite) not described in this specification is not particularly limited in terms of conditions and equipment used, and may be carried out according to a so-called conventional method.
[0091] Example
[0092] (Example 1)
[0093] When the contained Fe is converted into Fe2O3, the contained Zn is converted into ZnO, and the contained Mn is converted into MnO, the raw material powders weighed in such a manner that Fe2O3, ZnO and MnO become the ratios shown in Table 1 are mixed in a ball mill for 16 hours, and then pre-calcined at 900°C for 3 hours in the atmosphere, and cooled to room temperature over 1.5 hours in the atmosphere to prepare pre-calcined powder.
[0094] SiO2, CaO and Nb2O5 were weighed in amounts corresponding to 150, 700 and 250 ppm by mass, respectively, and added to the pre-calcined powder, followed by mixing and pulverizing for 12 hours using a ball mill to obtain pulverized powder.
[0095] Next, the pulverized powder was immersed in 0.1 mol / L ammonia water at a mass ratio of 0.6 for 1 hour, and after removing the ammonia water by filtration, water and polyvinyl alcohol were added to form a slurry, and the slurry was spray-dried to granulate. The granulated powder was sieved so that the particle size of the sample was roughly the same in the inventive example and the comparative example. The composition of the granulated powder was the same as that of the obtained ferrite.
[0096] The granulated powder thus obtained was quantified by the rotation torque value of the blades under the following conditions using a powder rheometer in two states: a loose bulk density state in which only the powder was filled but not vibrated and a state after vibrating 20 times. The ratio (torque ratio) of the torque value after vibrating 20 times divided by the torque value in the state in which only the powder was filled but not vibrated was obtained. The results are shown in Table 1.
[0097] Next, a pressure of 118 MPa was applied to the granulated powder to obtain a ring-shaped and E-shaped molded body. Then, these molded bodies were placed in a sintering furnace and sintered in a gas flow of nitrogen and air at a maximum temperature of 1320°C and a sintering time of 2 hours to obtain a sintered ring-shaped core body (N=3) with an outer diameter of 25 mm, an inner diameter of 15 mm, and a height of 5 mm, and a sintered E-shaped (E42 / 15) core body (N=100) with a long side of 42 mm, a short side of 21 mm, and a thickness of 15 mm. In addition, the E-shaped magnetic core was molded at a molding stroke of 15 pieces / min, and the target weight of the sintered core body was 45.0 g.
[0098] 《Method for measuring torque》
[0099] For loose bulk density: 44 g (corresponding to a height of about 51 mm when performing a reverse calculation) of a sample is allowed to fall naturally in a cylindrical glass container having an inner diameter of 25 mm and a volume of 25 mL.
[0100] For tap density: Repeat the operation of letting the sample filled to a loose bulk density fall naturally from a height of 4 cm 20 times (tap 20 times).
[0101] · Measurement apparatus: A powder rheometer FT4 manufactured by Freeman Scientific Inc. (blade rotation speed: 100 mm / s, blade diameter: 23.5 mm) was used.
[0102] Torque measurement: For loose bulk density and tap density, the blade of the FT4 was rotated and lowered to a specified height, and then raised and lowered to a specified height for 7 consecutive times. The torque was calculated from the flow energy of the 7th time. Furthermore, the torque ratio was calculated from the torque for loose bulk density and the torque for tap density.
[0103] The loss value of the annular core was obtained by the above method, and the average strength when the number of samples (all tested) was 100 and the occurrence rate of the cores below 300N were obtained for the M strength of the E-type (E42 / 15) core using Autograph in accordance with JIS C2560. The obtained results are recorded in Table 1. In addition, among all the standard samples, the weight of the E-type core after sintering was within the range of 45.0g±3% for all samples with N=100.
[0104] [Table 1]
[0105]
[0106] As shown in Table 1, in any of the standard samples according to the present invention, the surface of the granulated powder is smoothed by immersing the pulverized powder in an alkaline aqueous solution, thereby suppressing molding defects, and the average M strength and the occurrence rate of the core with significantly low M strength both show preferred values. Furthermore, when focusing on the magnetic properties, in Examples 1-1 to 1-5, the loss value at 100°C, 100kHz, and 200mT is 380kW / m 3 Therefore, it can be seen that all the inventive examples have both the above-mentioned high strength and suitable magnetic properties.
[0107] In contrast, in the comparative example containing less than 51.5 mol% of Fe2O3 (Comparative Example 1-1) and the comparative example containing more than 56.8 mol% of Fe2O3 (Comparative Example 1-2), although high toughness can be achieved, the magnetic anisotropy and magnetostriction become larger, so the loss value increases, and the loss value at 100°C, 100kHz, and 200mT does not meet 380kW / m 3 In addition, in the comparative examples (Comparative Examples 1-3) in which the amount of ZnO was insufficient compared to the range of the present invention, the Curie temperature increased excessively, and conversely, in the comparative examples (Comparative Examples 1-4) containing a larger amount of ZnO than the range of the present invention, the secondary peak of the loss showing the minimum value decreased, and in the above comparative examples, the loss values at 100°C, 100kHz, and 200mT did not satisfy 380kW / m 3 the following.
[0108] (Example 2)
[0109] When the contained Fe is converted into Fe2O3, the contained Zn is converted into ZnO, and further the contained Mn is converted into MnO, the raw materials are weighed in a manner having a component composition of Fe2O3: 53.0 mol%, ZnO: 12.0 mol% and MnO: 35.0 mol% (the same as Invention Example 1-2 of Example 1), mixed using a ball mill for 16 hours, pre-calcined at 900°C for 3 hours in the atmosphere, and cooled to room temperature after 1.5 hours in the atmosphere to prepare pre-calcined powder.
[0110] To the pre-calcined powder, SiO2, CaO and Nb2O5 were added in the amounts shown in the following Table 2, and CoO or NiO was added to a part of the sample, and mixing and pulverizing were performed for 12 hours using a ball mill to obtain pulverized powder.
[0111] Next, the pulverized powder was immersed in 0.1 mol / L ammonia water at a mass ratio of 0.6 for 1 hour, and after removing the ammonia water by filtration, water and polyvinyl alcohol were added to form a slurry, and the slurry was spray-dried to granulate. The granulated powder was sieved so that the particle size of the sample was roughly the same in the inventive example and the comparative example. The composition of the granulated powder was the same as that of the obtained ferrite.
[0112] The granulated powder thus obtained was subjected to a powder rheometer and the ratio (torque ratio) of the torque value after 20 taps divided by the torque value in the state of filling without tapping was determined in the same manner as in Example 1. The results are shown in Table 2.
[0113] Next, a pressure of 118 MPa was applied to the granulated powder to obtain a ring-shaped and E-shaped molded body. Then, these molded bodies were placed in a sintering furnace and sintered in a gas flow of nitrogen and air at a maximum temperature of 1320°C, a sintering time of 2 hours, and a sintered ring-shaped core body (N=3) with an outer diameter of 25 mm, an inner diameter of 15 mm, and a height of 5 mm, and a sintered E-shaped (E42 / 15) core body (N=100) with a long side of 42 mm, a short side of 21 mm, and a thickness of 15 mm. In addition, the E-shaped core body was molded at a molding stroke of 15 pieces / min, and the target weight of the sintered core body was 45.0 g.
[0114] The properties of each of these samples were evaluated using the same method and apparatus as in Example 1. The results are shown in Table 2. In all standard samples shown in Table 2, the weight of the E-shaped core after sintering was within the range of 45.0 g ± 3% for all samples with N = 100.
[0115] [Table 2]
[0116]
[0117] As shown in Table 2, in any standard sample according to the present invention, the surface of the granulated powder is smoothed by immersing the pulverized powder in an alkaline aqueous solution, thereby suppressing molding defects, and the average M strength and the occurrence rate of the core with significantly low M strength both show preferred values. Furthermore, when focusing on the magnetic properties, in the invention examples 2-1 to 2-11 in which the amounts of SiO2, CaO, Nb2O5, CoO and NiO are within the range of the present invention, the loss value at 100°C, 100kHz, and 200mT is 380kW / m 3 Therefore, it can be seen that all the inventive examples have both the above-mentioned high strength and suitable magnetic properties.
[0118] In contrast, it can be seen that in Comparative Examples 2-1, 2-3, and 2-5, in which only one of the three components of SiO2, CaO, and Nb2O5 is contained in a smaller range than the present invention, the grain boundary generation becomes insufficient, so the resistivity decreases, and the loss value deteriorates due to the increase in eddy current loss. In addition, it can be seen that in Comparative Examples 2-2, 2-4, and 2-6, in which only one of the above three components is excessive, the loss value deteriorates due to the appearance of abnormal grains, and the mechanical properties also deteriorate significantly.
[0119] (Example 3)
[0120] By the method shown in Example 1, raw materials were weighed, mixed, and pulverized so that the basic components and auxiliary components had the same composition as in Inventive Example 1-2 to prepare pulverized powder.
[0121] Standard samples were prepared in which the pulverized powder was immersed in an alkaline aqueous solution under the conditions shown in Table 3, and in which the pulverized powder was not immersed in an alkaline aqueous solution.
[0122] Polyvinyl alcohol was added to the treated pulverized powder or the untreated pulverized powder to perform spray drying and granulation. The granulated powder was sieved so that the particle size of the sample was substantially the same in the inventive example and the comparative example. The composition of the granulated powder was the same as that of the obtained ferrite.
[0123] The torque values of the granulated powders thus obtained were measured using a powder rheometer in the same manner as in Example 1, and the torque ratios were determined.
[0124] Next, a pressure of 118 MPa was applied to the granulated powder to obtain a ring-shaped and E-shaped molded body. Then, these molded bodies were placed in a sintering furnace and sintered in a gas flow of nitrogen and air at a maximum temperature of 1320°C, a sintering time of 2 hours, and a sintered ring-shaped core body (N=3) with an outer diameter of 25 mm, an inner diameter of 15 mm, and a height of 5 mm, and a sintered E-shaped (E42 / 15) core body (N=100) with a long side of 42 mm, a short side of 21 mm, and a thickness of 15 mm. In addition, the E-shaped core body was molded at a molding stroke of 15 pieces / min, and the target weight of the sintered core body was 45.0 g.
[0125] The properties of each of these samples were evaluated using the same method and apparatus as in Example 1. The weight of the E-shaped core after sintering was measured for all samples (N=100), and the number of samples outside the range of 45.0 g±3% was recorded. The obtained results are collectively recorded in Table 3.
[0126] [Table 3]
[0127]
[0128] In the invention examples 1-2, 2-7, 2-10 and 3-1 to 3-5 that meet the requirements of the present invention, the ratio (torque ratio) obtained by dividing the torque value after 20 vibrations by the torque value when not vibrated is as high as 1.7 or more, and a smooth granulated powder is obtained, so that cracks in the molded body can be suppressed. As a result, it can be seen that the average value of M strength is high and there are no samples with significantly low strength. In addition, since the friction between the granulated powders can be reduced, the filling weight when the granulated powder is filled into the mold is also stable, so even under the condition of a molding stroke as fast as 15 pieces / min, there will be no samples with a large deviation in weight.
[0129] On the other hand, in Comparative Example 3-1 in which the pulverized powder was not immersed in an alkaline aqueous solution, the surface smoothness of the granulated powder was poor because the binding force of the binder on the primary particles was not strengthened, so the ratio of the torque value after 20 vibrations divided by the torque value before vibration was as low as less than 1.7. Therefore, cracks were easily formed in the molded body, the average value of the M strength of the obtained core was low, and samples with significantly low M strength appeared. Furthermore, due to the influence of increased friction between the granulated powders, the mold filling amount during molding was unstable, and when the weight was measured in the state of the sintered core, samples outside the target range of 45.0g±3% appeared.
[0130] In addition, the uncompacted loose bulk density of Inventive Example 1-2 was 1.40 g / cm 3 The bulk density after 20 taps is 1.48 g / cm 3In contrast, the uncompacted loose bulk density of Comparative Example 3-1 was 1.38 g / cm 3 The bulk density after 20 taps is 1.44 g / cm 3 Therefore, the tap densities of Inventive Example 1-2 and Comparative Example 3-1 are almost the same.
[0131] Industrial Applicability
[0132] As described above, the MnZn ferrite specified in the present invention has the following characteristics: the loss value under the excitation conditions of 100°C, 100kHz, and 200mT is 380kW / m 3 The excellent mechanical properties of the sintered body E-type (E42 / 15) with high average M strength and no samples with significantly low strength are particularly suitable for use as magnetic cores for automotive electronic components.
Claims
1. A granulated powder for MnZn-based ferrite, which is composed of an iron compound, a zinc compound, a manganese compound, a silicon compound, a calcium compound, a niobium compound and inevitable impurities, When the total amount of the iron compound, the zinc compound and the manganese compound is 100 mol % in terms of Fe2O3, ZnO and MnO, the iron compound is 51.5 to 56.8 mol % in terms of Fe2O3, the zinc compound is 5.0 to 15.5 mol % in terms of ZnO, and the manganese compound is the balance in terms of MnO, The silicon compound is present in an amount of 50 to 300 ppm by mass in terms of SiO2, the calcium compound is present in an amount of 100 to 1300 ppm by mass in terms of CaO, and the niobium compound is present in an amount of 100 to 400 ppm by mass in terms of Nb2O5, relative to the total amount of the iron compound, the zinc compound, and the manganese compound. The torque ratio of the MnZn ferrite granulated powder is 1.7 or more.
2. The granulated powder for MnZn-based ferrite according to claim 1, wherein The MnZn ferrite granulated powder further contains at least one of a cobalt compound and a nickel compound. The cobalt compound is contained in an amount of 3500 mass ppm or less in terms of CoO, and the nickel compound is contained in an amount of 15000 mass ppm or less in terms of NiO, relative to the total amount of the iron compound, the zinc compound, and the manganese compound.
3. A method for producing a granulated powder for MnZn-based ferrite, which is a method for producing the granulated powder for MnZn-based ferrite according to claim 1, the method comprising the following steps: A pre-calcination step, pre-calcining a mixture of the iron compound, the zinc compound and the manganese compound to obtain a pre-calcined powder; a mixing-crushing step of adding a silicon compound, a calcium compound and a niobium compound to the pre-calcined powder, mixing the mixture and then crushing the mixture to obtain crushed powder; an immersion step of immersing the pulverized powder in an alkaline aqueous solution; and In the granulation step, a binder is added to the pulverized powder after the impregnation step, the mixture is mixed, and then granulated to obtain granulated powder.
4. A method for producing a granulated powder for MnZn-based ferrite, which is a method for producing the granulated powder for MnZn-based ferrite according to claim 2, the method comprising the following steps: A pre-calcination step, pre-calcining a mixture of the iron compound, the zinc compound and the manganese compound to obtain a pre-calcined powder; a mixing-crushing step, in which a silicon compound, a calcium compound and a niobium compound are added to the pre-calcined powder, and at least one of a cobalt compound and a nickel compound is further added and mixed, and then crushed to obtain a crushed powder; an immersion step of immersing the pulverized powder in an alkaline aqueous solution; and In the granulation step, a binder is added to the pulverized powder after the impregnation step, the mixture is mixed, and then granulated to obtain granulated powder.
5. A MnZn ferrite, which is composed of a basic component, an auxiliary component and inevitable impurities, When the total amount of iron, zinc and manganese in terms of Fe2O3, ZnO and MnO conversion of the basic components is 100 mol%, iron in terms of Fe2O3 conversion is 51.5-56.8 mol%, zinc in terms of ZnO conversion is 5.0-15.5 mol%, and manganese in terms of MnO conversion is the balance, In the auxiliary components, SiO2 is 50 to 300 mass ppm, CaO is 100 to 1300 mass ppm, and Nb2O5 is 100 to 400 mass ppm relative to the basic components. The minimum value of the M strength measured for 100 samples of sintered bodies of type E42 / 15 conforming to JIS C2560-3-1:2006 exceeded 300 N, and the average value was 600 N or more.
6. The MnZn-based ferrite according to claim 5, wherein: The auxiliary component further contains at least one of 3500 mass ppm or less of CoO and 15000 mass ppm or less of NiO relative to the basic component.
7. The MnZn-based ferrite according to claim 5 or 6, wherein: The loss value of the MnZn ferrite at 100°C, 100kHz and 200mT is 380kW / m 3 the following.
8. A method for producing a MnZn ferrite, which is a method for producing the MnZn ferrite according to claim 5, the method comprising the following steps: A pre-calcination step, pre-calcining a mixture of the iron compound, the zinc compound and the manganese compound to obtain a pre-calcined powder; a mixing-crushing step of adding a silicon compound, a calcium compound and a niobium compound to the pre-calcined powder, mixing the mixture and then crushing the mixture to obtain crushed powder; an immersion step of immersing the crushed powder in an alkaline aqueous solution; A granulation step, in which a binder is added to the pulverized powder after the impregnation step, the mixture is mixed, and then granulated to obtain granulated powder; as well as In the sintering step, the granulated powder is molded into a molded body, and then the molded body is sintered to obtain MnZn-based ferrite.
9. A method for producing a MnZn ferrite, which is a method for producing the MnZn ferrite according to claim 6, comprising the following steps: A pre-calcination step, pre-calcining a mixture of the iron compound, the zinc compound and the manganese compound to obtain a pre-calcined powder; a mixing-crushing step, in which a silicon compound, a calcium compound and a niobium compound are added to the pre-calcined powder, and at least one of a cobalt compound and a nickel compound is further added and mixed, and then crushed to obtain a crushed powder; an immersion step of immersing the crushed powder in an alkaline aqueous solution; A granulation step, in which a binder is added to the pulverized powder after the impregnation step, the mixture is mixed, and then granulated to obtain granulated powder; and In the sintering step, the granulated powder is molded into a molded body, and then the molded body is sintered to obtain MnZn-based ferrite.
Citation Information
Patent Citations
LOW LOSS MnZnNi-BASED FERRITE AND ELECTRONIC COMPONENT USING IT, AND SWITCHING POWER SUPPLY
JP2007051052A
Ferrite material
JP2012076983A
Ferrite sintered body
JP2014080344A
Mn-Zn-Ni-BASED FERRITE AND METHOD FOR PRODUCING THE SAME
JP2015036363A